PENERAPAN MODEL PEMBELAJARAN PICTURE AND PICTURE UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS V UPT SDN 13 PINRANG - Muttazam; Masnur; Nadar (STKIP Subang, 2026)
This study aims to describe the implementation steps of the Picture and Picture learning model and to measure the improvement of science (IPAS) learning outcomes on the topic of human developmental stages among fifth-grade students of UPT SDN 13 Pinrang. The research employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, conducted in two cycles, each consisting of planning, acting, observing, and reflecting. The subjects were 20 students of class VB in the 2025/2026 academic year. Data were collected through achievement tests, observation of teacher and student activities, interviews, and documentation, then analyzed using quantitative descriptive techniques (class mean and classical mastery) complemented by qualitative analysis. The findings show a consistent improvement across cycles. The class mean rose from 66.75 in the pre-cycle to 73.75 in Cycle I and 86.75 in Cycle II, while classical mastery increased from 25% (5 of 20 students) to 55% (11 students) and finally 95% (19 students). Student learning activity also improved from 68.75% (fair) in Cycle I to 86.75% (very good) in Cycle II. These results confirm that the systematic and consistent application of the Picture and Picture model, which integrates concrete visual media with logical image sequencing and collaborative discussion, effectively enhances students' science learning outcomes at the elementary level.